APPLICATION MODELING PROGRAM "ELCUT" FOR RESEARCH ELECTROMAGNETIC CHARACTERISTICS INDUCTION SYSTEMS. - Чемерис, В.; Марінченко, Г. (Science-based technologies, 2011)
Abstract Induction systems of solenoid type used in pulse drives of translational motion and in magnetic-pulse devices for processing of metal products have been researched in the paper at different relative positions of primary solenoid and secondary system, consisting of a central ferromagnetic core and conductive tubes (workpieces) stands on it, at using of external electromagnetic screens of different types for reducing of the harmful effects of scattered magnetic fields. It is shown that screening of inductor slightly changes relative electromagnetic force of axial interaction between the primary and secondary systems, but it has significant affect on the magnitude of the radial magnetic pressure, which exerts on the workpiece. Comparative parameters of screens made of steel, copper or aluminum in combination with steel are presented.